Test of Antimicrobial Activity of Rimbang Leaf (Solanum torvum) Ethanol Extract on Escherichia coli and Candida albicans - Aura Iga Maharani; Rahmatul Huda Asra; Aulia Yunita; Resti Desmayanti; Husnul Khatimah; Dwi Hilda Putri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Aims: One of the types of traditional medicinal plants is rimbang (Solanus frowned). Rimbang is often used as an alternative medicine by rural communities because it is useful as a medicine for coughs, wounds, fever, boils and scabs. Rimbang leaf extract is known to contain flavonoids and tannins (polyphenolic) which have antimicrobial properties. The purpose of this study was to prove rimbang leaf extract was able to inhibit growth E.coli and C.albicans. Methods: Rimbang leaf extraction was carried out by maceration for three days with 96% ethanol solvent. Then evaporate using rotaryevaporator until thick extract is formed. The antimicrobial activity test was carried out by the agar diffusion method using disc paper by measuring the diameter of the inhibition zone for bacterial growth. The test concentrations used varied from 50%, 25%, 12.5%, 6.25% and 3.125%. Result: The results showed that rimbang leaf extract had antimicrobial activity against E.coli and C.albicans Main Conclusion: The antimicrobial activity test with strong inhibition was found in E. coli with a concentration of 6.25% an inhibition zone diameter of 12.15 mm, moderate inhibition at a concentration of 3.125% with an inhibition zone diameter of 9.5 mm, and moderate inhibition on C. albicans concentration of 50% with an inhibition zone diameter